PROGRAM APPLICATION IMPRESSIONS AND CINEMA FILM SYNOPSIS USING VISUAL BASIC 6.0 - Fahmi Drajat; Don Elsafitra, SKom (Jurnal Sistem Informasi, 2000)
The use of computers as a tool to solve human problems is felt more and more increasing. This is supported by the emergence of a programming language that supports OOP techniques (Object Oriented Programming). With the OOP, the job becomes much easier to program than ever before. Examples of programming languages that have supported this facility from Microsoft Visual Basic.In order to meet the demands and needs of programmers, Microsoft continues to influence this programming language. At the center of this writing the final version of Visual Basic is Microsoft Visual Basic version 6.0.In this writing, the author uses the Microsoft Visual Basic version 6.0 to create a software application that can be usedin movie theaters.